A DETERMINANTS OF FINANCIAL BEHAVIOR ON ACCOUNTING STUDENT - Wirawan ED Radianto; Tommy C. Effrata; Liliana Dewi (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This study examines the impact of financial literacy, financial knowledge, locus of control, financial attitude, financial self-efficacy, and mental accounting on financial behavior. The study sample is an accounting student. There are 159 questionnaires that can be processed in total out of 250 distributed to the accounting selected at random. Hypothesis testing was conducted using multiple regression analysis. The result of the study shows that locus of control, financial attitude, financial self-efficacy, and mental accounting has a positive impact on financial behavior. However, this study found that financial literacy and financial knowledge do not affect financial behavior. This study also found that mental accounting has the most influence on financial behavior. This research contributes that mental accounting enables students to manage finances and make financial decisions.